2021
DOI: 10.1016/j.jad.2020.12.113
|View full text |Cite
|
Sign up to set email alerts
|

The role of only-child status in the psychological impact of COVID-19 on mental health of Chinese adolescents

Abstract: Background The impact of coronavirus disease (COVID-19) on public mental health in 2019 is verified, but the role of only-child status in the mental health of adolescents confined at home during the COVID-19 epidemic has not been investigated and is not clear. Objective Our study aims to assess the impact of only-child status on the mental health of adolescents confined at home during the COVID-19 outbreak. The exposure risk to COVID-19, adverse experience, parent-child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 30 publications
5
42
0
1
Order By: Relevance
“…Prevalence of anxiety in cross‐sectional studies ranged from a low of 8% (China) (Yue et al., 2020 ) to as high as 74% (Egypt) (Alamrawy et al., 2021 ). Studies with lower estimates of anxiety (8%–25%) tended to only include younger children and adolescent populations (<12 years) (de Avila et al., 2020 ; Xie et al., 2020 ; Xue et al., 2021 ; Yue et al., 2020 ) and/or take place approximately more than six weeks after the initial enactment of regional lockdown measures (Cao et al., 2021 ; Shitao Chen, Cheng, & Wu, 2020 ; Li et al., 2021 ; Ravens‐Sieberer et al., 2021 ; Tang, Xiang, Cheung, & Xiang, 2021 ; Zhang, Ye, et al., 2020 ; Zhang, Zhang, et al., 2020 ). Mid‐to‐high estimates of anxiety (34%–74%) were more frequently observed in studies conducted within six weeks of the initial lockdown restrictions in the region (Giannopoulou et al., 2021 ; Qi, Zhou, et al., 2020 ; Yeasmin et al., 2020 ; Zhou, Wang, et al., 2020 ; Zhou, Zhang, et al., 2020 ) and/or in studies that focused on older adolescents (>15 years) (Chi et al., 2021 ; Giannopoulou et al., 2021 ; Lu et al., 2020 ), as well as during periods of high local COVID‐19 case counts (Alamrawy et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence of anxiety in cross‐sectional studies ranged from a low of 8% (China) (Yue et al., 2020 ) to as high as 74% (Egypt) (Alamrawy et al., 2021 ). Studies with lower estimates of anxiety (8%–25%) tended to only include younger children and adolescent populations (<12 years) (de Avila et al., 2020 ; Xie et al., 2020 ; Xue et al., 2021 ; Yue et al., 2020 ) and/or take place approximately more than six weeks after the initial enactment of regional lockdown measures (Cao et al., 2021 ; Shitao Chen, Cheng, & Wu, 2020 ; Li et al., 2021 ; Ravens‐Sieberer et al., 2021 ; Tang, Xiang, Cheung, & Xiang, 2021 ; Zhang, Ye, et al., 2020 ; Zhang, Zhang, et al., 2020 ). Mid‐to‐high estimates of anxiety (34%–74%) were more frequently observed in studies conducted within six weeks of the initial lockdown restrictions in the region (Giannopoulou et al., 2021 ; Qi, Zhou, et al., 2020 ; Yeasmin et al., 2020 ; Zhou, Wang, et al., 2020 ; Zhou, Zhang, et al., 2020 ) and/or in studies that focused on older adolescents (>15 years) (Chi et al., 2021 ; Giannopoulou et al., 2021 ; Lu et al., 2020 ), as well as during periods of high local COVID‐19 case counts (Alamrawy et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies targeted primary school populations (<12 years) (Alonso-Mart ınez et al, 2021; Chen, Chen, et al, 2020; de Avila et al, 2020;Dumas, Ellis, & Litt, 2020;Fontenelle-Tereshchuk, 2020;A. Gassman-Pines et al, 2020;Glynn, Davis, Luby, Baram, & Sandman, 2021;Lee, Ward, Chang, & Downing, 2021;Romero, L opez-Romero, Dom ınguezalvarez, Villar, & G omez-Fraguela, 2020;Waller et al, 2021;Xie et al, 2020;Xue et al, 2021), 27 reported on middle and high school populations (aged 12-18) (Alamrawy et al, 2021;Breaux et al, 2021;Buzzi et al, 2020;Cao et al, 2021;Chi et al, 2021;Ellis, Dumas, & Forbes, 2020;Fish et al, 2020;Giannopoulou, Efstathiou, Triantafyllou, Korkoliakou, & Douzenis, 2021;Janssen et al, 2020;Kılınc ßel, Kılınc ßel, Muratda gı, Aydın, & Usta, 2020;Li et al, 2021;Liebana-Presa et al, 2020;Lu et al, 2020;Luthar, Ebbert, & Kumar, 2020;Magson et al, 2021;Masuyama, Shinkawa, & Kubo, 2020;Murata et al, 2021;Oosterhoff, Palmer, Wilson, & Shook, 2020;Pons et al, 2020;Qi, Liu, et al, 2020;Qi, Zhou, et al, 2020;Rauschenberg et al, 2020;Rogers et al, 2021;Scott et al, 2021;Secer & Ulas, 2020;…”
Section: Age Distributionmentioning
confidence: 99%
“…In particular, it is critical to investigate implications of the pandemic on the parent-child relationship among families with infants, given the known importance of developing attachment security in the first years of life for future attachment security [ 24 ] and future child development [ 25 , 26 , 27 ]. Initial research into the role of the parent-child relationship during the COVID-19 pandemic has found attachment security to be a protective factor for adolescent depression and anxiety symptoms during the March 2020 outbreak of COVID-19 in China [ 28 ], which is an early indication of the importance of secure parent-child relationships in pandemic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is supported by a previous Italian study (Agnelli Foundation, 2020 ), which shows that even proper methods and technologies would make little sense in socio-culturally disadvantaged contexts. Moreover, we found that the presence of siblings had a negative effect on lessons and homework; it may be related to the fact that the only children usually receive larger amounts of feedbacks and attention from their parents and this is assumed to strengthen their self-confidence (Cao et al, 2021 ), improving their school performance as a result. Furthermore, availability of technology devices and quiet environments are supposed to be more difficult to find in large families and/or little homes, making attention harder to keep.…”
Section: Discussionmentioning
confidence: 92%